From psychology to spirituality = De la psychologie à la spiritualité - Malette, Judith, 1963-; Rovers, Martin W.; Sundaram, Lakshmi (Conflict, ethics, and spirituality ;, 2019)
This book explores the diverse dimensions of the links between psychology and spirituality. The first section explores the historic evolution of these links, sometimes tense, often polysemous but that nevertheless leave few indifferent. The second section explores how the integration of psychology and spirituality can be fostered to deepen the understanding of sexual abuse, couples psychotherapy and ethics. Lastly, the final section presents three empirical studies. These studies researched the links between psychology and spirituality through the lens of three distinct populations: Vietnamese immigrants, bisexual Christian women and elderly persons. The conclusion underlines the importance of using a multidimensional conceptualisation of human beings and considering the psychological, physical, ethical and spiritual aspects as essential components of being human.00Le présent livre explore diverses dimensions des liens entre la psychologie et la spiritualité. La première section du livre porte sur l?évolution historique de ces liens, parfois tendus, souvent polysémiques, mais qui ne laissent personne indifférent ... La seconde section présente comment l?intégration de la spiritualité et de la psychologie peut s?appliquer dans la compréhension de l?abus sexuel, en psychothérapie de couple et en éthique professionnelle. Enfin, trois études empiriques composent la dernière section. Chacune d?entre elles a étudié les liens entre la psychologie et la spiritualité tels qu?ils sont vécus chez trois populations distinctes : des immigrants Vietnamiens, des femmes bisexuelles chrétiennes et des personnes âgées. La conclusion souligne l?importance, voire le caractère essentiel, des dimensions psychique, physique, éthique et spirituelle dans la conceptualisation de l?être humain.0.